Processing and early age properties of 3D printed sustainable concrete - Ho, Garrick Sze Jian (Nanyang Technological University, 2020)
3D Concrete Printing (3DCP) has been around for several years now and it one technique that can minimize waste, man hours and costs with productivity, safety and sustainability being improved at the same time. Previously Panda [1] has shown that 50% OPC/FA with 0.35% water showed the best properties as compared to having higher FA content. In this report, 50% FA/OPC will be used with addition of 2 admixtures polycarboxylate ether (PCE) and hydroxypropyl methylcellulose (HPMC) to improve buildability and workability. This report presents the early age properties and processing of a 3D printable and sustainable mix design that consists of PCE and HPMC. Processing of the design mixes are done through the use of 3 tests, namely rheometer test, printing test and direct shear test (DST). Unlike conventional construction casting, 3DCP do not have formwork. Concrete is deposited layer by layer above one another. Each layer has to hold its own weight and the weight above. Before deposition, concrete must first pass through a pump and to reach its desired printing location. Therefore, rheology of fresh concrete is important to determine if the material is pumpable and buildable. Rheology properties such as static yield stress (SYS), dynamic yield stress (DYS), viscosity and thixotropic properties are obtained using 3ITT, step-down protocols along with the Bingham model. Design mixes with low DYS and high SYS are labelled to be optimum mixes those properties are preferred in 3DCP. Printing tests are carried out to determine the buildability of each mixture with a slender cylinder design. Cohesion values and combined inter particle friction is said to be linked to the ‘green strength’ of fresh concrete that allows it to carry their own weight after mixing or compacting. Mechanical behavior was found to be similar to that of soil [2], thus, the Mohr coulomb yield criterion is adopted in this report. Cohesion values can be obtained through the use of Direct Shear Test (DST) which is a test civil engineers used on soil. Characterization of layers and the cohesion can be used to predict future failures when printing the printing parameters.